It is given that h(x)=fog(x) and h(x)=4(x+1)^2.
So it follows:
![\text{fog(x)}=4(x+1)^2](https://img.qammunity.org/2023/formulas/mathematics/college/auccecgratgic8cxsqafm2aukkukkyvy9s.png)
For option A, f(x)=x+1,g(x)=4x^2
So the value of fog(x) is given by:
![f(g(x))=g(x)+1=4x^2+1](https://img.qammunity.org/2023/formulas/mathematics/college/va0bpwikrhd8g9tw3sxci84wunsmpm5130.png)
So A is incorrect.
For option B, f(x)=(x+1)^2,g(x)=4x^2
So the value of fog(x) is given by:
![f(g(x))=g(x)+1=(g(x)+1)^2=(4x^2+1)^2](https://img.qammunity.org/2023/formulas/mathematics/college/65irzgixmubbvjn98uidaaae6z7lit5lkd.png)
So B is incorrect.
For option C, f(x)=4x^2,g(x)=x+1
So the value of fog(x) is given by:
![f(g(x))=4\lbrack g(x)\rbrack^2=4(x+1)^2](https://img.qammunity.org/2023/formulas/mathematics/college/rcb5xft3lu2kpfto1l5smkzciikbnw8anj.png)
So C is correct.